(untitled) (Dhaka University Journal of Biological Sciences, 2011)
Leaf extract of Citrus aurantifolia exhibited remarkable inhibitor effect on the radial mycelial growth of Neurospora crassa. The extract also showed mutagenic effect and atleast six morphological mutants of the fungus were detected including albino (al 243), vigorous (vg 117), fluffy (fl 220), colonial (cl 232), conidial band (con. band 171) and dirty (dir 83). The mutants were used for estimation of soluble protein in comparison with the wild type (Ema). The soluble protein content increased to some extent in case of the mutants con. band 171 (192.86 μg/ml), cl 232 (188.57 μg/ml) and vg 117 (186.43 μg/ml) as compared to the wild type (182.14 μg/ml). On the other hand, the soluble protein content was remarkably decreased in case of the mutant al 243 (94.28 μg/ml), which was about 50% less than the control. This indicates that the leaf extract not only effect colony morphology but possesses profound effect on growth and metabolism of the fungus. Key words: Neurospora crassa; Mutation; Leaf extract; Soluble protein DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8958 DUJBS 2010; 19(2): 151-155